2004
DOI: 10.3132/dvdr.2004.011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and cardiovascular disease: the role of PPARγ activators beyond their anti-diabetic action

Abstract: O ver the past few years it has been recognised that insulin resistance (IR) is an independent risk factor for major cardiovascular events. In addition, IR is associated with other factors such as hypertension, dyslipidaemia and endothelial dysfunction, and this cluster of metabolic disorders contributes to the cardiovascular risk of patients with IR. Given the increasing number of patients with IR, the modulation of their cardiovascular risk is a major task in diabetology and vascular medicine. This review wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 84 publications
1
13
1
1
Order By: Relevance
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 43%
“…In models of diabetes mellitus and cardiovascular disease, activation of PPAR-␥ has been shown to restore vascular structure and correct endothelial dysfunction, [17][18][19] resulting in a reduction in the elevated blood pressure associated with hypertensive conditions. 20 -22 In the present study, administration of the PPAR-␥ agonist rosiglitazone to RUPP rats ameliorated both hypertension and endothelial dysfunction via a HO-1-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthers, PPARγ activation leads to the following responses within the vasculature: (a) in ECs, it inhibits endothelial inflammation by suppressing inflammatory gene expression, (b) in VSMCs, it inhibits proliferation and migration, and promotes apoptosis, and (c) in macrophages, it suppresses inflammation by regulating gene expression and increases cholesterol uptake and efflux. The literature on these beneficial effects of PPARγ activation has been extensively reviewed elsewhere (Bishop-Bailey, 2000;Duan et al, 2008;Li and Palinski, 2006;Marx et al, 2004;Schiffrin, 2005;Touyz and Schiffrin, 2006;Walcher and Marx, 2004).…”
Section: Pparγ In Vascular Cellsmentioning
confidence: 99%
“…Several lines of evidence suggest that endothelial dysfunction plays a key role in the development of both macro-and microangiopathy in patients with inflammatory-associated diseases as atherosclerosis, hypercholesterolemia, hypertension, stroke, and diabetes, as well as in animal models of these diseases (Cai and Harrison, 2000;Kobayashi et al, 2000, Landmesser et al, 2004Matsumoto et al, 2003Matsumoto et al, , 2004bMatsumoto et al, , 2005Triggle et al, 2003). Although the genesis of this endothelial dysfunction and its associated vasomotor abnormalities remains poorly understood, there have been recent demonstrations that in cardiovascular diseases, activation of PPARγ not only has cardio-protective effects, but also restores vascular structure and corrects endothelial dysfunction (Bishop-Bailey, 2000;Li and Palinski, 2006;Schiffrin, 2005;Touyz and Schiffrin, 2006;Walcher and Marx, 2004). Because of these beneficial effects, a given activator of PPARγ may have a therapeutic potential for the prevention of cardiovascular diseases that lies beyond its actions on carbohydrate and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation